Non‐Lithographic Fabrication of All‐2D α‐MoTe2 Dual Gate Transistors. (16th March 2016) - Choi, Kyunghee; Lee, Young Tack; Kim, Jin Sung; Min, Sung‐Wook; Cho, Youngsuk; Pezeshki, Atiye; Hwang, Do Kyung; Im, Seongil
Abstract : As one of the emerging new transition‐metal dichalcogenides materials, molybdenum ditelluride (α‐MoTe2 ) is attracting much attention due to its optical and electrical properties. This study fabricates all‐2D MoTe2 ‐based field effect transistors (FETs) on glass, using thin hexagonal boron nitride and thin graphene in consideration of good dielectric/channel interface and source/drain contacts, respectively. Distinguished from previous works, in this study, all 2D FETs with α‐MoTe2 nanoflakes are dual‐gated for driving higher current. Moreover, for the present 2D dual gate FET fabrications on glass, all thermal annealing and lithography processes are intentionally exempted for fully non‐lithographic method using only van der Waal's forces. The dual‐gate MoTe2 FET displays quite a high hole and electron mobility over ≈20 cm 2 V −1 s −1 along with ON/OFF ratio of ≈10 5 in maximum as an ambipolar FET and also demonstrates high drain current of a few tens‐to‐hundred μA at a low operation voltage. It appears promising enough to drive organic light emitting diode pixels and NOR logic functions on glass. Abstract : All‐2D MoTe2 ‐based dual gate field‐effect trasnsistors (FETs) are fabricated on glass, using hexagonal boron nitride and graphene without thermal annealing and lithography processes. The dual‐gate MoTe2 FET drives a few tens‐to‐hundred μA at a low operation voltage. It nicely demonstrates its capability of OLED pixel switching and NOR logic operation.